Feasibility Study on Establishment of Eats Tea Time in Quezon City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Eats Tea Time tea house is a new tea room in the quaint of San Bartolome, Novaliches, Quezon City. The love and knowledge of teas will make the transition to running a tea house a natural step. The knowledge of the health benefits of tea will help the marketing and sales efforts. The tea house will offer a range of hot teas and pastries and snacks for take-out. Most of the respondents already have an idea of what kind of beverages they want because of the marketing efforts of other businesses. At the same time, fashion is always on the move –not which fancy drinks are so widely accepted, savvy consumers are looking for new, more unique treats to enjoy. In San Bartolome, various types of potential clientele are divided among residents, employees, and students. The researchers expect to generate sales to existing committed tea drinkers, who will immediately recognize the quality of the products and services. Marketing to large local groups who are already familiar with teas will emphasize the atmosphere, value, and wide array of potential promos. Sales to students, employees, and residents depend on a highly visible location, quaint charm, and promotional efforts. The business is expected to gain more and more profit every year. The study expects to catch the interests of loyal customers due to the variety of drinks and foods offered. The finished product is deemed viable and feasible. The business aims to offer its products at a competitive price to meet the demand of middle-to higher-income local market area residents, employees, and students.
Keywords: tea, health, business